2019
DOI: 10.3892/ol.2019.10740
|View full text |Cite
|
Sign up to set email alerts
|

Tumor‑derived exosomes educate fibroblasts to promote salivary adenoid cystic carcinoma metastasis via NGF‑NTRK1 pathway

Abstract: Salivary adenoid cystic carcinoma (SACC) is a rare head and neck malignancy characterized by unpredictable expansion, considerable perineural invasion and high risk of metastasis; however, the underlying mechanism of SACC progression remains unclear. Cancer-associated fibroblasts localized within the tumor microenvironment may promote cancer malignant transformation by enhancing tumor growth, blood vessel formation, inflammation development and metastasis occurrence. Small extracellular vesicles, including exo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Similar to gene fusion, the aberrant expression of NTRKs gene is a critical event in cancers. NTRK1 promoted proliferation and metastasis of cancer cells and lead to poor prognosis in multiple cancers [14][15][16][17][18], while it suppressed cell proliferation in neuroblastoma [19]. NTRK2 was shown to serve as an oncogene in multiple cancers [20][21][22][23], and its increased expression was associated with poor outcome [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to gene fusion, the aberrant expression of NTRKs gene is a critical event in cancers. NTRK1 promoted proliferation and metastasis of cancer cells and lead to poor prognosis in multiple cancers [14][15][16][17][18], while it suppressed cell proliferation in neuroblastoma [19]. NTRK2 was shown to serve as an oncogene in multiple cancers [20][21][22][23], and its increased expression was associated with poor outcome [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…performed transcriptome RNA sequencing and reverse transcriptome quantitative polymerase chain reaction analysis on human periodontal ligament fibroblasts (HPLFs) that had ingested salivary adenoid cystic carcinoma cell-derived EVs, and the results confirmed that HPLFs were cultured as a pre-tumorigenetic phenotype [33] . This phenomenon is associated with EV-mediated stimulation of proinflammatory cytokines and secretion of nerve growth factor (NGF) [33] . In addition, secretion analysis of EVs collected from Hodgkin's lymphoma (HL) cells revealed enhanced release of pro-inflammatory cytokines (such as IL-1α, IL-6, and TNF-α), growth factors (G-CSF and GM-CSF), and pro-angiogenic factors (such as VEGF) [34] .…”
Section: Cancer-associated Fibroblasts (Cafs)mentioning
confidence: 83%
“…Xu et al. performed transcriptome RNA sequencing and reverse transcriptome quantitative polymerase chain reaction analysis on human periodontal ligament fibroblasts (HPLFs) that had ingested salivary adenoid cystic carcinoma cell-derived EVs, and the results confirmed that HPLFs were cultured as a pre-tumorigenetic phenotype [33] . This phenomenon is associated with EV-mediated stimulation of proinflammatory cytokines and secretion of nerve growth factor (NGF) [33] .…”
Section: Cancer-associated Fibroblasts (Cafs)mentioning
confidence: 97%
“…Moreover, exosomes carrying miR-122 released by breast cancer cells reduced glucose uptake by normal recipient cells in pre-metastatic niche, increasing nutrient supply for metastatic cells Fong et al, 2015 ). Then, the metastatic effect by TEVs can also be mediated by their effect in stromal cells like fibroblasts ( Fang et al, 2018 ; Xu et al, 2019 ); macrophages ( Liang et al, 2019 ; Zhao et al, 2020 ) and in bone stroma ( Dai et al, 2019 ) at long distances ( Figure 1B ).…”
Section: Tevs As Important Mediators Of Cell Communication During Malignant Transformation and Tumor Progressionmentioning
confidence: 99%